Penerapan Laporan Keuangan Entitas Nonlaba Berdasarkan Isak 35 (Studi Kasus di Gereja Kristus Raja Seon Kabupaten Malaka) - Manek, Antonius Darwanto; Bahri, Syamsyul; Kojanah, Kojanah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This study aims to analyze the implementation of financial reporting for non-profit entities based on the Interpretation of Financial Accounting Standards (ISAK) 35 at the Church of Christ the King Seon. As a non-profit organization in the religious sector, the church is required to prepare financial statements that comply with the applicable accounting standards. This research uses a qualitative approach to explain the phenomenon being studied in depth. Data was collected through direct observation, interviews, and documentation related to the preparation of the church’s financial statements. The analysis results indicate that the Church of Christ the King Seon has not fully implemented ISAK 35 in its financial reporting. Several non-compliance indicators were found, including an improper financial statement format, incomplete and unstructured presentation of financial information, and inappropriate use of accounting terms. Non-compliance with ISAK 35 can lead to various negative impacts, such as difficulties in understanding the financial statements, challenges in comparing financial performance with other organizations, and doubts about the church's credibility and accountability. This study recommends that the Church of Christ the King Seon promptly adjust its financial reporting according to ISAK 35 to enhance transparency, accountability, and trust among stakeholders.